2015
DOI: 10.3109/10715762.2015.1016429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of (-)-epigallocatechin-3-gallate on glucose-induced human serum albumin glycation

Abstract: (−)-Epigallocatechin-3-gallate (EGCg) is a naturally occurring polyphenol found in plant-based foods and beverages such as green tea. Although EGCg can eliminate carbonyl species produced by glucose autoxidation and thus can inhibit protein glycation, it is also reported to be a pro-oxidant that stimulates protein glycation in vitro. To better understand the balance between antioxidant and pro-oxidant features of EGCg, we evaluated EGCg-mediated bioactivities in a human serum albumin (HSA)/glucose model by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A stock solution of tannin was prepared in water. Because used compound slightly absorb UV light the values of fluorescence intensity received from experiments were corrected (using below equation) to avoid inner filter effect [30,31]:…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…A stock solution of tannin was prepared in water. Because used compound slightly absorb UV light the values of fluorescence intensity received from experiments were corrected (using below equation) to avoid inner filter effect [30,31]:…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…Application of an antioxidant or inhibition of lipid peroxidation products MDA, 4-HNE, and other carbonyl toxic compounds are effective methods to inhibit the formation of aging-related amyloid. Tea polyphenols, especially EGCG, have significant antioxidant and carbonyl capture activities [45]. Catechins account for approximately 50-80% of tea polyphenols, and they all have 2-phenylbenzopyran as the main structure.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in previous reports, Abdullah et al [26] found that pyridoxamine could effectively reduce the electrophoretic mobility of glycated HSA medicated by glucose. Min et al [35] indicated that the molecular weight enhancement and protein dispersion of glycated HSA were alleviated by epigallocatechin gallate.…”
Section: Effect Of Ea and Uroa-urod On The Molecular Weight Of Hsamentioning
confidence: 99%